Pengaruh Kualitas Pelayanan dan Citra Perusahaan terhadap Loyalitas Deposan di Bank BRI Syariah KCP Majalaya - Ayu Lestari; Faisal Rakhman (Ma'soem University, 2022)
Based on the results of the initial research, that the background of this research is the fluctuating number of depositors at Bank BRI Syariah KCP Majalaya. This is suspected to have something to do with service quality and company image on depositor loyalty. This study aims to find out how the Quality of Service on Loyalty of Depositors at Bank BRI Syariah KCP Majalaya, how the influence of Corporate Image on Loyalty of Depositors at Bank BRI Syariah KCP Majalaya, and to find out how the influence of Service Quality and Corporate Image on Loyalty of Depositors at Bank BRI Syariah KCP Majalaya. The object of research in this report is to measure the Loyalty of Depositors at Bank BRI Syariah KCP Majalaya, while the type of research is quantitative associative, the type of data is primary data and uses data collection techniques in the form of observations, interviews, literature studies, and questionnaires. While the sampling technique is non-probability sampling, with a total population of depositors at Bank BRI Syariah KCP Majalaya. The results showed that there was a significant effect between Service Quality on Loyalty of Depositors, which was 56.5% or tcount > ttable (9.599 > 1.994), there was a significant influence between Corporate Image and Loyalty of Depositors, which was 28.4% or tcount > ttable. (5.307 > 1.994), and simultaneously there is a significant influence between Service Quality and Corporate Image on Loyalty of Depositors at Bank BRI Syariah KCP Majalaya, namely 58% or Fcount > Ftable (48.251 > 3.13).